Cotton fiber: a powerful single-cell model for cell wall and cellulose research - Haigler, Candace H.; Betancur, Lissete; Stiff, Michael R.; Tuttle, John R. (Frontiers in Plant Science, 2012)
Cotton fibers are single-celled extensions of the seed epidermis. They can be isolated in pure form as they undergo staged differentiation including primary cell wall synthesis during elongation and nearly pure cellulose synthesis during secondary wall thickening. This combination of features supports clear interpretation of data about cell walls and cellulose synthesis in the context of high throughput modern experimental technologies. Prior contributions of cotton fiber to building fundamental knowledge about cell walls will be summarized and the dynamic changes in cell wall polymers throughout cotton fiber differentiation will be described. Recent successes in using stable cotton transformation to alter cotton fiber cell wall properties as well as cotton fiber quality will be discussed. Future prospects to perform experiments more rapidly through altering cotton fiber wall properties via virus induced gene silencing will be evaluated.